Software Composition c - Gschwind, Thomas; Paoli, Flavio; Gruhn, Volker; Book, Matthias; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The book constitutes the refereed proceedings of the 11th International Conference on Software Composition, SC 2012, held in Prague, Czech Republic, in May/June 2012, co-located with TOOLS 2012 Federated Conferences. The 12 revised full papers were carefully reviewed and selected from 42 submissions for inclusion in the book. The papers reflect all current research in software composition and are organized in topical sections on software composition in specification languages; context-aware and dynamic composition; composition in software development; and applications of software composition.
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Computer Science; Software Engineering; Programming Techniques; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Computer Communication Networks; Mathematical Logic and Formal Languages